Digital Literacy in Determining Gen Z's Political Choices in the 2024 Election - Muhamad Arif Setiawan (Universitas Islam Negeri Raden Fatah Palembang, 2025)
Digital literacy brings new meaning to the context of political choice. It is also seen as capable of guiding digital users in using social media. However, the reality is the opposite when it comes to political choice behavior, as voting behavior is complex and diverse in its application. This study aims to determine Gen Z's voting behavior and the factors influencing it using qualitative descriptive research methods. The results indicate that friendships remain the strongest factor in determining Gen Z's political choices in the region studied. The presence of social media is limited to providing information and entertainment for its users.